Long-Term Efficacy and Safety of Leflunomide in Large-Vessel Giant Cell Arteritis: A Single-Center, 10-Year Experience. Issue 1 (20th January 2021) - Tomelleri, Alessandro; Coath, Fiona; Sebastian, Alwin; Prieto-Pena, Diana; Kayani, Abdul; Mo, Jonathan; Dasgupta, Bhaskar
Abstract : Supplemental digital content is available in the text.